LEVEL OF KNOWLEDGE ABOUT RESEARCH IN STUDENTS OF THE ACCOUNTING SCIENCES FACULTY - UNMSM - Chumpitaz Ramos, Domingo Gúzman (2017)
The research aims to describe the level of research knowledge of the Accounting Faculty Sciences students of the UNMSM (2016). A questionnaire designed to carry out the field work was applied to the students of the last year of the Accounting Sciences Faculty. Of the total number of students, a sample of 153 students was taken, 76 students were from the Accounting Professional Academic School, 38 Tax Management students and 38 Business and Public-Sector Audit students. Stratified sampling and simple random sampling were performed. The results show that it is necessary to strengthen the research in the students of the Faculty of Accounting Sciences. We also found that there are no significant differences in the level of knowledge in research of the students by specialty of the Accounting Sciences Faculty of the UNMSM. This result is confirmed by doing a Chi-square test.